Downregulation of CHIP promotes ovarian cancer metastasis by inducing Snail‐mediated epithelial–mesenchymal transition - Sun‐Mi Park; Seung‐Ho Park; Ki‐Jun Ryu; In‐Kyu Kim; Hyeontak Han; Hyo‐Jin Kim; Seon‐Hee Kim; Keun‐Seok Hong; Hyemin Kim; Minju Kim; Bok Im Cho; Jeong Doo Heo; et al. (Molecular Oncology)
The epithelial–mesenchymal transition (EMT) plays a pivotal role in the conversion of early‐stage tumors into invasive malignancies. The transcription factor Snail, an extremely unstable protein whose subcellular levels are regulated by many E3 ubiquitin ligases, promotes EMT as well as associated pathological characteristics including migration, invasion, and metastasis. Through yeast two‐hybrid screening, we identified the carboxyl terminus of Hsc70‐interacting protein (CHIP) as a novel Snail ubiquitin ligase that interacts with Snail to induce ubiquitin‐mediated proteasomal degradation. Inhibition of CHIP expression increases Snail protein levels, induces EMT, and enhances in vitro migration and invasion as well as in vivo metastasis of ovarian cancer cells. In turn, Snail depletion abrogates all phenomena induced by CHIP depletion. Finally, Snail and CHIP expression is inversely correlated in ovarian tumor tissues. These findings establish the CHIP–Snail axis as a post‐translational mechanism of EMT and cancer metastasis regulation.